2016
DOI: 10.1007/s10530-016-1082-9
|View full text |Cite
|
Sign up to set email alerts
|

Complex patterns of global spread in invasive insects: eco-evolutionary and management consequences

Abstract: The advent of simple and affordable tools for molecular identification of novel insect invaders and assessment of population diversity has changed the face of invasion biology in recent years. The widespread application of these tools has brought with it an emerging understanding that patterns in biogeography, introduction history and subsequent movement and spread of many invasive alien insects are far more complex than previously thought. We reviewed the literature and found that for a number of invasive ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 142 publications
6
111
0
2
Order By: Relevance
“…In a landscape still not completely colonized by an invasive pathogen, the connectivity may be increased by additional introductions, which also have the potential to introduce new genotypes [80,81], or by insect vectors that may actively or passively spread the pathogen over long distances. Fusarium circinatum Nirenberg and O'Donnell, the causal agent of pitch canker, is a potentially dangerous invasive pathogen in pine (Pinus sp.)…”
Section: Connectivitymentioning
confidence: 99%
“…In a landscape still not completely colonized by an invasive pathogen, the connectivity may be increased by additional introductions, which also have the potential to introduce new genotypes [80,81], or by insect vectors that may actively or passively spread the pathogen over long distances. Fusarium circinatum Nirenberg and O'Donnell, the causal agent of pitch canker, is a potentially dangerous invasive pathogen in pine (Pinus sp.)…”
Section: Connectivitymentioning
confidence: 99%
“…This considerable amount of mitochondrial genetic diversity for an exotic insect is likely to have resulted either from a single introduction of a large number of individuals, or from multiple introductions over time, both of which occur with some regularity in invasive organisms (Garnas et al, 2016;Nadel et al, 2010). (Hurley et al, 2010).…”
Section: Genetic Structure Of the Pissodes Species In South Africamentioning
confidence: 99%
“…Forest ecosystems are increasingly threatened by invasive insect pests whose spread has been dramatically increased through the movement of wood products and packaging materials, as well as live plant material (Aukema et al, 2011;Tobin, 2015). It has also been shown that multiple introductions frequently increase genetic diversity of many introduced insects, including forest pests (Cognato et al, 2015;Garnas et al, 2016;Nadel et al, 2010). In addition, multiple introductions may allow unintended introductions of different lineages of the same species or cryptic species, as has been shown for the woodwasp, Sirex noctilio (Boissin et al, 2012), and the eucalyptus leaf weevil, Gonipterus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of invasion has important evolutionary consequences for invasive populations, affecting the genetic diversity of the initial colonisers (Blows & McGuigan 2015;Colautti & Lau 2015). The genetic history of invasive insects frequently shows that the process has not occurred as a single population simply establishing in a new area (Garnas et al 2016), and multiple invasions can add to the complexity of the genetic structure of invasive populations (Blackburn et al 2011;Walther et al 2009). In such situations, there is potential for secondary contact and the subsequent admixture of genetically distinct and previously allopatric insect populations (Dlugosch et al 2015;Garnas et al 2016).…”
Section: Introductionmentioning
confidence: 99%